Small interfering RNA target for long noncoding RNA PCGEM1 increases the sensitivity of LNCaP cells to baicalein. Issue 8 (2nd July 2020) - Han, Zeping; He, Jinhua; Zou, Maoxian; Chen, Weiming; Lv, Yubing; Li, Yuguang
Abstract: The objective of this study is to investigate the inhibitory effect and mechanism of long noncoding RNA PCGEM1 siRNA combined with baicalein on prostate cancer LNCaP cells. LNCaP cells transfected with small hairpin RNA lentiviral vector targeting PCGEM1 were constructed and their expression in LNCaP cells was absent. The stable cell line of LNCaP cells infected with LV3‐shRNA‐PCGEM1 was successfully constructed. In addition, LV3‐shRNA‐PCGEM1 was able to increase the baicalein‐induced inhibitory effects on LNCaP cells, and the susceptibility was 2.3 fold higher than that of baicalein alone. LV3‐shRNA‐PCGEM1 combined with baicalein also inhibited the colony formation, increased G2 and S phase cells, inhibited the expression of PCGEM1, and induced autophagy of LNCaP cells. In summary, LV3‐shRNA‐PCGEM1 may improve the sensitivity of LNCaP cells to baicalein, and the molecular mechanism may be associated with the decrease of PCGEM1 expression and the induction of autophagy. Our findings provided an experimental basis for the combined treatment of Chinese traditional and Western medicine on prostate cancer in a clinical setting.